Health-Related Quality of Life and Its Correlation With Depression Among Chinese Centenarians - Han, Ke; Yang, Shanshan; Jia, Wangping; Wang, Shengshu; Song, Yang; Cao, Wenzhe; Wang, Jianwei; Liu, Miao; He, Yao (Frontiers in Public Health, 2020)
Background: As evidence on depression and health-related quality of life (HRQoL) among the oldest-old is currently limited, this study aimed to re-examine the association between depression and HRQoL among centenarians. Methods: We analyzed cross-sectional data from the China Hainan Centenarian Cohort Study (CHCCS). The 15-item Geriatric Depression Scale (GDS-15) and EuroQol five dimensions-visual analog scale (EQ-5D-VAS) were used to evaluate depression and HRQoL, respectively. Poor health states were defined as EQ-5D index<0.665. Based on their GDS-15 score, individuals were categorized into three stages of depression: major depressive disorder (MDD; score ≥10), minor depressive disorder (MnDD; score between 6 and 9), and normal (score ≤5). Based on sex and comorbidity stratification, multivariable logistic regression was used to calculate the risk of poor health state in different levels of depression. We also used restricted cubic splines with a knot at 5 points (GDS-15) to flexibly model the association of GDS-15 scores with poor health states. Results: Totally, 1,002 participants were included in this study for analysis. Participants’ median age was 102 years, and 82.04% were female. The median EQ-5D index was 0.68 (range, -0.149 to 1), and the mean VAS and GDS-15 scores were 61.60 (range: 0 to 100) and 5.23 (range: 0 to 15), respectively. Centenarians with MnDD and MDD accounted for 38.12% and 9.98%, respectively. While those with poor health states accounted for 45.11%. For every 1-point increase in GDS-15, the risk of poor health state increased by 20% (P<0.001) after an adjustment for age, gender, ethnicity, marital status, education, residence type, smoking, drinking, weekly exercise, BMI category, serum albumin, 25-hydroxyvitamin D, C-reactive protein, and comorbidities. MnDD and MDD were independent risk factors for poor health state (MnDD, OR=2.76, P<0.001; MDD, OR=3.14, P<0.001). The association was more prominent in male centenarians and centenarians without comorbidity. Conclusions: This study demonstrated a negative association between depression and HRQoL in Chinese centenarians, especially in male centenarians and centenarians without comorbidity. Large-scale prospective studies are needed to corroborate our findings and provide more information about the causal inference and internal mechanisms of this association.